Evaluation of Heating and Cooling Loads for a Well-Insulated Single-Family House under Variable Climate Pattern - Prozuments Aleksejs (Sciendo, 2021)
Single family houses consume substantially more thermal energy per floor area compared to multi-apartment buildings to satisfy space heating or cooling demand. Over the past decades there has been an undisputed evidence of a temperature rise across the world that has led to a growing concern of more extreme weather patterns and regular seasonal heat waves globally. As such, building occupants are at a continuously growing risk to overheating exposure inside the premises. Within the framework of this study a single-family house was examined with respect to its thermal performance in warm and cold seasons. A simulation model was developed in IDA-ICE software to evaluate annual thermal energy demand for a reference scenario, 3 shading scenarios and for an optimized scenario. At an optimized scenario that incorporates mechanical ventilation with a heat recovery unit and enhanced thermal performance of the external building elements, the annual thermal energy demand in the proposed single-family house was reduced by 39.5 % compared to the reference scenario, which is a significant step towards meeting nearly zero energy building criteria.